2010
DOI: 10.1021/ie901171b
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Phenolic Compounds from Aqueous Solutions onto Chitosan-Coated Perlite Beads as Biosorbent

Abstract: Chitosan-coated perlite (CCP) beads were prepared by dropwise addition of a liquid slurry containing chitosan and perlite to an alkaline bath. The resulting beads were characterized using Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), and surface area analysis. The chitosan content of the beads is 23% as determined by a pyrolysis method. Adsorption of phenolic compounds (phenol, 2-chlorophenol, and 4-chlorophenol) from aqueous solutions on chitosan-coated perlite beads was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…The results revealed that Langmuir sorption isotherm was a more linear model than Freundlich for the sorption of mandelic acid enantiomers on RMBAG‐SCMPs because correlation Langmuir coefficients (R 2 ) ​​are greater than Freundlich. The important features of the Langmuir sorption isotherm parameter can be used to foresee the affinity between the sorbates and sorbent using a dimensionless constant called a separation factor or equilibrium parameter ( R L ), which is expressed by the following relationship RL=11+bC0 where b (L/mg) is the Langmuir constant and C 0 (mg/L) is the initial concentration of mandelic acid enantiomers. The value of R L indicated the type of Langmuir isotherm to be irreversible ( R L = 0), linear ( R L = 1), unfavorable ( R L > 1), or favorable (0 < R L < 1) .…”
Section: Resultsmentioning
confidence: 99%
“…The results revealed that Langmuir sorption isotherm was a more linear model than Freundlich for the sorption of mandelic acid enantiomers on RMBAG‐SCMPs because correlation Langmuir coefficients (R 2 ) ​​are greater than Freundlich. The important features of the Langmuir sorption isotherm parameter can be used to foresee the affinity between the sorbates and sorbent using a dimensionless constant called a separation factor or equilibrium parameter ( R L ), which is expressed by the following relationship RL=11+bC0 where b (L/mg) is the Langmuir constant and C 0 (mg/L) is the initial concentration of mandelic acid enantiomers. The value of R L indicated the type of Langmuir isotherm to be irreversible ( R L = 0), linear ( R L = 1), unfavorable ( R L > 1), or favorable (0 < R L < 1) .…”
Section: Resultsmentioning
confidence: 99%
“…The absorption bands at 3449 cm -1 which appeared on all materials spectra is due to overlapping of the OH and N-H stretching vibration of functional groups engaged [14][15] in hydrogen bond [16]. The bands at 3264 and 3109 cm −1 which appeared on chitin spectrum only related to vibrational modes involved in intermolecular hydrogen bonding CO• • •HN and the intramolecular bonds of NH groups, respectively [17].…”
Section: Characterization Of Chitosanmentioning
confidence: 99%
“…The D-R model given by Kumar et al (2010) was used to determine the mechanism of adsorption of 3-methyl-4nitrophenol onto CS-based nanofibres. The equations used to make the linear plots for the model are as follows:…”
Section: Mechanism Of Adsorptionmentioning
confidence: 99%
“…The adsorption mean-freeenergy E was used for this purpose. E is the free energy required to transfer 1 mol of the adsorbate from the solution to the surface of the adsorbent (Kumar et al, 2010). The magnitude of E is therefore used to estimate whether the interaction between the adsorbate and the adsorbent is physical or chemical.…”
Section: Mechanism Of Adsorptionmentioning
confidence: 99%